Factors influencing COVID-19 preventive behavior in Thanlyin township, Yangon region, Myanmar - Moh, Myo M.; Win, Hla H.; Aung, May S.; Soe, Le Thandar (International Journal Of Community Medicine And Public Health, 2024)
Background: The World Health Organization (WHO) has identified COVID-19 as a novel lung condition caused by an emerging virus. Socioeconomic factors significantly influence preventive behaviors like handwashing, wearing masks, social distancing, coughing cover, and avoiding touching the face to reduce COVID-19 transmission. Aim was to determine factors influencing COVID-19 preventive behavior among selected households. Methods: The cross-sectional descriptive study with 700 samples was conducted from July 2022 to December 2023 that collected quantitative data using an interviewer-administered questionnaire that was converted to Open Data Kit, a mobile data tool in Thanlyin Township, Yangon, Myanmar. Objective of study was to determine the association between socio-demographics, knowledge and preventive COVID-19 behaviors in this township residence over the age of 18 years old. One-way analysis of variance (ANOVA), independent t-test, and multiple linear regression were used to analyze the data. Results: The overall mean score of knowledge related to COVID-19 was 25.95±7.07, whereas 37.48±15.05 was for preventive behaviors. After multiple linear regression, participants who living in urban, single, passed high educational status, family members who had COVID history, COVID-19 patients who had underlying diseases reported higher preventive behavior where as participants who had co morbidity reported lower performing preventive COVID-19 behaviors. Those participants with higher knowledge scores reported higher preventive COVID-19 behaviors (β=0.312, p=0.000). Conclusions: Public health interventions should utilize these experiences to effectively communicate and promote preventive measures, thereby enhancing the targeting and impactful nature of future infectious disease prevention efforts.